Psychometric Analysis: Validation of the ASCDI Instrument for Traditional Craft SMEs - Harry Yulianto (Yayasan Cerdas Pedia Indonesia, 2026)
Digital transformation presents a challenge and an opportunity for traditional craft SMEs, requiring adaptation without eroding cultural values. This study aims to develop and validate the Adaptive Socio-Cultural Digital Innovation (ASCDI) instrument to measure socio-cultural digital innovation capacity and enterprise resilience. The instrument development method involved 350 traditional craft SMEs in Makassar through several stages: content validation by experts, empirical testing, exploratory and confirmatory factor analysis, and reliability testing. The results produced a final instrument consisting of 30 items divided into six dimensions: Adaptive Digital Literacy, Socio-Cultural Preservation, Collaborative Governance (for the innovation capacity variable), and Business Competitiveness, Cultural Sustainability, and Market Expansion (for the resilience variable). All items proved to meet content validity (Aiken's V > 0.80), construct validity (loading factor > 0.70), and excellent reliability (Cronbach's Alpha = 0.949). The validated and reliable ASCDI instrument was expected to be a dependable measurement tool for researchers, practitioners, and policymakers in assessing and developing sustainable digital innovation strategies for traditional craft SMEs.